PROBLEMATIKA GURU DALAM MENINGKATKAN KEMAMPUAN LITERASI SISWA PADA KELAS II SDN 1 MEDANA TAHUN PELAJARAN 2023 - Ainun Isthifha Darma (STIT Al-Aziziyah, 2023)
Basic literacy learning is a concrete step for teachers to improve student learning abilities so that they are able to support student activities in the learning process in the classroom. The aims of this study were 1) to analyze the implementation of basic literacy learning for students in grade II SDN 1 Medana; 2) To analyze the obstacles experienced by the teacher in learning the basic literacy of reading and writing students in class II of SDN 1 Medana: 3) To provide solutions that are used by the teacher to overcome the obstacles experienced in learning the basic literacy of reading and writing students in class II of SDN 1 Medana. The method used in this research is to use a qualitative research approach. The data collection used in this study is the method of interviews, observation and documentation. While the data analysis uses the stages of data collection, data presentation, and conclusions. The results of this study are: 1) Implementation of basic literacy learning to read and write students in class II SDN 1 Medana. Implementation of basic literacy learning in elementary schools at low grades requires teacher readiness both in terms of competence, especially pedagogic competence, especially when teachers teach in elementary schools. Because elementary school is the most important institution in increasing each student's interest, talent and motivation so that they are able to develop each competency they have, namely cognitive, affective and psychomotor through learning basic literacy (reading and writing: 2) Obstacles experienced by teachers in learning basic literacy reading and writing students in class II SDN 1 Medana. Obstacles experienced by teachers in learning basic literacy consist of internal factors, namely consisting of students and teachers. While external factors consist of the library and school and family environment: 3) Solutions used by teachers to overcome obstacles experienced in learning basic literacy in reading and writing students in class II SDN 1 Medana. The solutions used in overcoming the problems faced by teachers in the implementation of basic literacy learning lead to increasing the competence of teachers and students so that they can work together in increasing the basic literacy abilities of students in schools in the learning process seen from the internal side. As for the external side, it leads to mileu (environment) which is able to support student activities in learning, besides the library which is another support.